Type of Communication and Organization Climate Affecting the Change Management of the One of Five Stars Hotel Employees at Pattaya City - Manpaen, Naruenart; Siriwongse, Tongfu; Chinachoti, Pavin (Journal of Modern Learning Development, 2023)
The objectives of this study were: 1. To study the Type of Communication of a five-star hotel staff at Pattaya City. 2. To study the Organization Climate of a five-star hotel staff at Pattaya City. 3. To study Change Management of employees of a five-star hotel at Pattaya City. 4. To study Change Management classified by Demographic factors of employees of a five-star hotel at Pattaya City. 5. To study Type of Communication and Organization Climate affecting the Change Management of employees in a five-star hotel at Pattaya City. The sample used in the study were 223 employees of a five-star hotel at Pattaya city by answering questionnaires. The statistics used in data analysis consisted of frequency, percentage, mean, standard deviation, T-test, F-test and Multiple regression analysis. The results of the study revealed that 1. Type of Communication the overall is at a high level and the overall opinion of employees was Upward communication, Diagonal communication and Horizontal communication. 2. Organization Climate the overall is at a high level and the overall opinion of employees was organizational structure. 3. Change management the overall is at a high level and the Change Management the overall opinion of employees was the organization informed the personnel about the need to make changes. 4. Change management classified by demographic factors was found that the demographic factors were different affecting the Change Management were not different. 5. Type of Communication and Organization Climate affected the change management was found that the Type of Communication and Organization Climate had a statistically significant effect to change management.